Expression of epithelial growth factor receptor as a protein marker in oral reticular and erosive lichen planus - Keshani, Forooz; Kargahi, Neda; Nikbakht, Mohammad Hossein; Najafi, Shekufe; Fallah, Fateme (BMC oral health, 2024)
Oral lichen planus (OLP) is a chronic inflammatory mucosal disease that is classified as a premalignant condition. Epithelial growth factor receptor (EGFR) is associated with tumorigenesis and tumor progression and is overexpressed in several oral malignant disorders. Despite the association of EGFR overexpression with oral potentially malignant lesions, few studies have analyzed its expression in OLP, showing controversial results. This study aimed to compare the expression of EGFR as a protein marker in Reticular and Erosive OLP. This descriptive-analytical cross-sectional was conducted on 15 paraffin blocks of reticular lichen planus lesions, 16 paraffin blocks of erosive OLP lesions, and 8 paraffin blocks of inflammatory fibrous hyperplasia lesions as the control group (39 in total). After immunohistochemical staining for EGFR, samples were simultaneously observed by two maxillofacial pathologist, and the percentage of stained cells, intensity of staining, pattern of staining, and the location of stained cells were obtained. The Mann-Whitney-U test showed that there was no significant difference in the mean percentage of stained cells between erosive OLP and reticular OLP (P-value = 0.213) and between reticular OLP and control group (P-value = 0.137), but there was a significant difference between erosive OLP and control group (P-value = 0.035). Fisher's exact test showed that there was no significant difference between the frequency distribution of staining patterns in three types of lesions (P-value = 0.90). Kruskal-Wallis test showed that there was no significant difference between the intensity of staining in the three groups (P-value = 0.19) and also there was no significant difference between the location of stained cells in different layers of the epithelium in the three groups (P-value = 0.90). The results of this study showed that in comparison of reticular OLP, erosive OLP, and the control group there was a significant difference just between erosive OLP and control group in the percentage of stained cells.